TALMEH IN MASHRAB POETRY (Academicia Globe: Inderscience Research, 2022)
The article analyzes the role of the art of talmeh in the works of Baburahim Mashrab on the basis of examples. In this way, the poet's goal is to reveal the ideological and artistic significance of talmeh in his poetry.